A Case of Self-treatment Induced Recurrent Fixed Drug Eruptions Associated with the Use of Different Fixed Dose Combinations of Fluoroquinolone-Nitroimidazole - Pal, Agnik (Iran J Med Sci, 2014)
A young male patient used fixed dose combinations of different fluoroquinolones and nitroimidazoles several times in the last few years for self-treating repeated episodes of diarrhea and loose motion. Each time, he experienced fixed drug eruptions that increased in number and severity on subsequent occasions. Suspecting association between the drug and the rashes, the patient each time discontinued the treatment prematurely, and preferred to switch to a similar formulation next time, but with different molecules of fluoroquinolone (ciprofloxacin or ofloxacin) and nitroimidazole (tinidazole or ornidazole). He could not however avoid the rash. This time the patient presented with multiple, round-to-oval, well-defined, hyperpigmented cutaneous patches of different dimensions, all over the body. He appeared to have run out of options and therefore consulted us seeking advice on how he should treat himself next time he suffered from diarrhea. Causality assessment by Naranjo’s algorithm revealed a definite relationship between the cutaneous adverse reaction and the offending drug. He was counselled regarding medication in general and advised, in particular, to avoid the tendency to self-treat any future episode of diarrhea.